Shattered - Patterson, James, 1947-; Born, James O. (2022)
"Nothing could tear Detective Michael Bennett away from his new bride--except the murder of his partner and best friend. NYPD master homicide investigator Michael Bennett and top FBI abduction specialist Emily Parker have a history. Working case after case, each can predict the other's next move. So when she fails to show at FBI headquarters in Washington, DC, Bennett risks venturing far outside his jurisdiction. The investigation he undertakes is the most brilliant detective work of his career... and the most intensely personal. A portrait begins to emerge of a woman as adept at keeping secrets as forging powerful connections. A woman whose enemies had both the means and the motives to silence the real Emily Parker--and her protectors"--
Includes an excerpt for Blowback by James Patterson and Brendan Dubois (pages 3-17 at end of work)
Keywords: Bennett, Michael -- (Fictitious character) -- Fiction; Police -- New York (State) -- New York -- Fiction; Murder -- Investigation -- Fiction; Young women -- Crimes against -- Fiction; New York (N.Y.) -- Fiction; Detective and mystery fiction; Thrillers (Fiction); Novels